2017
DOI: 10.18632/oncotarget.17663
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral depletion of regulatory T cells using CD25-targeted photodynamic therapy in a mouse melanoma model induces antitumoral immune responses

Abstract: Tumor immunotherapy aims to overcome the immunosuppressive microenvironment within tumors, and various approaches have been developed. Tumor-associated T regulatory cells (Tregs) suppress the activation and expansion of tumor antigen-specific effector T cells, thus, providing a permissive environment for tumor growth. Therefore, optimal strategies need to be established to deplete tumor-infiltrated Tregs because systemic depletion of Tregs can result in reduced anti-tumor effector cells and autoimmunity. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…We performed flow cytometric analysis as described previously ( Oh et al, 2017a ). In brief, single cells were pretreated with α-CD16/32 Ab (2.4 G; TONBO Bioscience) and stained with the following Abs: α–mouse Foxp3 (FJK-16s; eBioscience), α–mouse CD8α (53-6.7; BD Biosciences), α–mouse CD11b (M1/70; BD Biosciences), α–mouse CD4 (GK1.5; BioLegend), or α–mouse CD45.2 (104; TONBO Bioscience).…”
Section: Methodsmentioning
confidence: 99%
“…We performed flow cytometric analysis as described previously ( Oh et al, 2017a ). In brief, single cells were pretreated with α-CD16/32 Ab (2.4 G; TONBO Bioscience) and stained with the following Abs: α–mouse Foxp3 (FJK-16s; eBioscience), α–mouse CD8α (53-6.7; BD Biosciences), α–mouse CD11b (M1/70; BD Biosciences), α–mouse CD4 (GK1.5; BioLegend), or α–mouse CD45.2 (104; TONBO Bioscience).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to blocking CTLA4 receptors as abovementioned, another strategy has been developed to directly and specifically deplete the local Treg cells by taking advantage of the targeting specificity of antibodies. For example, conjugating Ce6 photosensitizer to anti‐CD25 antibody allowed targeted PDT against Treg cells while minimally affecting neighboring cell populations or tissues . In this study, an intratumoral injection of the Ce6‐anti‐CD25 resulted in localized depletion of Treg cells and consequently, improved the infiltration of CD8 + T cells.…”
Section: Pdt Cancer Immunotherapymentioning
confidence: 69%
“…In this study, an intratumoral injection of the Ce6‐anti‐CD25 resulted in localized depletion of Treg cells and consequently, improved the infiltration of CD8 + T cells. The authors further examined the level of the infiltrated CD8 + T cells by measurement of its cytokines secretion especially IFN‐γ, and discovered a fivefold higher level of IFN‐γ for mice with depleted Treg cells . Kobayashi et al also reported success in Treg immunodepletion with only IR700 conjugated F(ab′) 2 fragments generated from an anti‐CD25 antibody .…”
Section: Pdt Cancer Immunotherapymentioning
confidence: 99%
“…It is also worth mentioning that selective elimination of intra-tumoral Tregs is sufficient to bolster cytotoxic killing of tumor cells without perturbing the systemic immune system. Using a technique called photodynamic therapy, this was demonstrated by aiming a laser beam at tumors to deplete only tumor-resident Tregs that were pre-bound with a photosensitizer-conjugated antibody against CD25, a dominant Treg surface marker [ 22 ]. A similar result from deleting glucocorticoid-induced tumor necrosis factor receptor (GITR)-expressing Tregs would have added more credence, on the grounds that anti-GITR treatment strongly reversed the growth of advanced tumors [ 23 ].…”
Section: From Friend To Foe—regulatory T-cell (Treg) Induction Of mentioning
confidence: 99%